The Influence of Role Playing Methods on Early Childhood Language Development - Rokhani, Nuri (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to determine the influence of role playing learning methods on the language development of group B students in RA Diponegoro 203 Gunungwetan. The approach in this study is Classroom Action Research, which is a controlled investigation process to find and solve classroom learning problems. The problem-solving process is carried out cyclically, with the aim of improving the quality of learning and learning outcomes in certain classes. The subjects of the study were group B RA Diponegoro 203 Gunungwetan Jatilawang which amounted to 33 children. The basis for the selection of research subjects is because it is based on observation and deliberation of teachers about children's language skills. Data analysis is carried out descriptively on student achievement in learning. The results of data analysis show that the learning carried out to improve children's language skills in RA Diponegoro 203 before the role play method was applied was not optimal. The implementation of learning has not been well programmed, teachers carry out routine learning activities with less varied methods, such as storytelling, conversation, and question and answer methods. The media used in learning is less interesting because it only listens to the teacher's story. A considerable increase occurred in cycle II, namely in the indicator that children can respond to speech, can start conversations with the media that plays a role